2005
DOI: 10.1002/cncr.20767
|View full text |Cite
|
Sign up to set email alerts
|

Mcl‐1 expression in gestational trophoblastic disease correlates with clinical outcome

Abstract: BACKGROUND Hydatidiform moles (HMs) are abnormal pregnancies with a propensity for developing persistent disease in the form of gestational trophoblastic neoplasia (GTN), which requires chemotherapy. In previous studies, the authors demonstrated that low apoptotic activity was correlated with the progression of HM to GTN, and they hypothesized that some apoptosis‐related genes may determine this progression. METHODS The differential expression of apoptotic genes in HMs that subsequently developed into GTN was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…22,23,37 In this study, we found an inverse correlation between ASPP1 expression and clinical progress of hydatidiform moles. It is possible that the progressive loss of proapoptotic ASPP1 expression hinders the usual enhanced apoptosis in cytotrophoblasts and villous intermediate trophoblasts, leading to the development of persistent gestational trophoblastic neoplasms.…”
Section: Aberrant Expression and Hypermethylation Of Aspp1 In Gestatisupporting
confidence: 54%
“…22,23,37 In this study, we found an inverse correlation between ASPP1 expression and clinical progress of hydatidiform moles. It is possible that the progressive loss of proapoptotic ASPP1 expression hinders the usual enhanced apoptosis in cytotrophoblasts and villous intermediate trophoblasts, leading to the development of persistent gestational trophoblastic neoplasms.…”
Section: Aberrant Expression and Hypermethylation Of Aspp1 In Gestatisupporting
confidence: 54%
“…Total RNA was extracted from frozen tissue by Trizol (Invitrogen, Carlsbad, CA) with integrity checked by gel electrophoresis. 10 Only samples with rRNA (28S/18S) ratio between 1.8 and 2 were used.…”
Section: Tissue Preparation and Rna Extractionmentioning
confidence: 99%
“…Our study using the Atlas™ Human Apoptosis Array (Clontech; Palo Alto, CA), which includes 205 cDNA related to apoptosis, identified Mcl-1 to be a predictive factor for GTN. 10 By using combined cDNA suppression subtractive hybridization (SSH) technique and microarray analysis in the current study, we attempted to expand the identification of differentially expressed genes in HM that subsequently developed GTN when compared with HM that spontaneously regressed. 11 The SSH technique is sensitive and efficient for generating cDNA highly enriched for differentially expressed genes with both high and low abundance, because this technique combines both the suppression PCR amplification and cDNA subtraction, leading to generation of two subtractive libraries.…”
mentioning
confidence: 98%
“…2 6 7 Recently, we used apoptotic cDNA arrays, and identified Mcl-1, an apoptosis related gene, as being related to the clinical progression of HM. 8 In our present study, we compared the gene expression profiles of normal first trimester placentas and choriocarcinoma cell lines using more comprehensive cDNA arrays, followed by confirmatory gene expression studies by quantitative reverse transcription polymerase chain reaction (RT-PCR) and immunohistochemistry. The results were correlated with the clinicopathological and biological parameters in an attempt to improve our understanding of the pathogenesis of GTD.…”
mentioning
confidence: 99%